Perkembangan Pasraman Hindu sebagai Daya Tarik Pariwisata - I Gede Sutarya (UHN IGB Sugriwa Denpasar, 2018)
Hindu ashram is a formal and informal center for Hindu education. Ashram which become the attraction of foreign tourists is informal ashram. Ideally, this ashram is a center of Hindu education, but foreign tourists are also using this facility. This raises the problem of research in the form of development, attractiveness and development model. This research was conducted qualitatively, with descriptive statistics. The theory used is the theory of tourist attraction and tourism area life cycle. Through this theory explained that the development of Hindu ashram in Bali tourism is very massive since 2006. The main attraction of Hindu ashram is aspiritual guru. Therefore, the model of development should start from the strengthening of local gurus by supporting for strengthening public transportation. The strengthening of this local guru should start because the Hindu ashram hasentered the involvement stage according to the tourism area life cycle theory